Sterilization Evaluation And Traffic Management Of Tual Crossing Port In Maluku Province - Oktrianti Diani; Windi Nopriyanto; Rizky Rewa (IWJ : Inland Waterways Journal, 2021)
The Tual Ferry Terminal serves 21 routes between islands and between provinces with pioneer routes. However, at this time many people and unauthorized vehicles can easily enter the port area, causing the port to become less regulated, such as traders selling their wares in the port area, delivery / pick-up entering the port dock area. This is due to the absence of a zoning system in accordance with the Regulation of the Minister of Transportation Number: 29 of 2016 concerning the Sterilization of Ferry Ports. So that in the activity of getting on and off of passengers and loading and unloading vehicles, there are several obstacles, among others, the absence of zoning at the port which causes unauthorized people to enter restricted areas and irregular traffic flow patterns. This research aims to; 1) Dividing Zones of Areas needed for Passengers and Vehicles 2) Regulating the Pattern of Vehicle Traffic at the Tual Ferry Port. 3) And To Determine Equipment That Can Help In Handling Zoning Arrangements at the Tual Ferry Port. The research methodology used is direct observation in the field (field research) with measurement studies and literature (literature). Then to analyze this, refer to PM Number 29 of 2016 concerning Ferry Port Sterilization. The analysis used is the zoning analysis, analysis of vehicle and passenger traffic patterns and the equipment needed to support the zone system. The results of this study are 1) That the sterilization of passengers and vehicles is a zone arrangement system at the crossing port from the accumulation of passengers and vehicles. 2) Whereas the existing conditions of the Tual Ferry Port in Maluku province are not in accordance with the Regulation of the Minister of Transportation Number 29 of 2016 concerning the Sterilization of Ferry Ports. 3) And to regulate passenger and vehicle traffic by optimizing officers and adding signs to facilitate the departure and arrival process.